3(2d-8)=11d-18(d-3)

Simple and best practice solution for 3(2d-8)=11d-18(d-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2d-8)=11d-18(d-3) equation:


Simplifying
3(2d + -8) = 11d + -18(d + -3)

Reorder the terms:
3(-8 + 2d) = 11d + -18(d + -3)
(-8 * 3 + 2d * 3) = 11d + -18(d + -3)
(-24 + 6d) = 11d + -18(d + -3)

Reorder the terms:
-24 + 6d = 11d + -18(-3 + d)
-24 + 6d = 11d + (-3 * -18 + d * -18)
-24 + 6d = 11d + (54 + -18d)

Reorder the terms:
-24 + 6d = 54 + 11d + -18d

Combine like terms: 11d + -18d = -7d
-24 + 6d = 54 + -7d

Solving
-24 + 6d = 54 + -7d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '7d' to each side of the equation.
-24 + 6d + 7d = 54 + -7d + 7d

Combine like terms: 6d + 7d = 13d
-24 + 13d = 54 + -7d + 7d

Combine like terms: -7d + 7d = 0
-24 + 13d = 54 + 0
-24 + 13d = 54

Add '24' to each side of the equation.
-24 + 24 + 13d = 54 + 24

Combine like terms: -24 + 24 = 0
0 + 13d = 54 + 24
13d = 54 + 24

Combine like terms: 54 + 24 = 78
13d = 78

Divide each side by '13'.
d = 6

Simplifying
d = 6

See similar equations:

| 2(x-5)=180 | | 7x+4x+12=33 | | 7+4q=10+3q | | d/8=3.5 | | 3(2x)+3(x)=2700 | | -222+17x-4x=168 | | -15+3x=8(1+x)+2 | | 14(3c-6)=7c-9 | | -7+5(-2x-4)= | | -13-7n=-6 | | 11(4p+4)-4p=4(7p-7) | | a+15.5=45 | | 36=8-14 | | 0.25(7+3r)=-12.5r | | (5x-4)/(5x+4)-2/3 | | 4/5+3/5 | | 7a+5+2a-2=4a+3-5a | | 5.4x+1=4.4x | | 3/4(12c-4)=15c+15 | | 4(8-2x)=24 | | S=100-80*100 | | 5x+8y=45 | | x^2+12x+54= | | 3v+2v=5(2+v) | | 54=2(w*.5)+2w | | 1/3x+7=10 | | 5(w-4)-9=-5(-5w+9)-8w | | 9z=8z+1 | | (5t+1)/8=(t+6)/16+(t-4)/16 | | 54=2(w*5)+2w | | 70/14 | | cx^2+6x=x^3-cx |

Equations solver categories